Developing the Chinese version of the new 5-level EQ-5D descriptive system: the response scaling approach - Luo, Nan (Springer Netherlands, 2012)
PURPOSE: To develop a Chinese version of the new, 5-level EQ-5D descriptive system (EQ-5D-5L) from the existing EQ-5D-3L by identifying Chinese label wording suitable for constructing EQ-5D-5L’s 5-point response scales. METHODS: In face-to-face interviews, perceived severity of selected Chinese labels when they were used to describe EQ-5D health problems was measured from 50 native Chinese speakers using a 0 (no problems) to 100 (the worst problems) visual analog scale. Selection of label wording was based on the severity scores and semantic similarity with label wording used in the existing English and Spanish EQ-5D-5L. RESULTS: The severity scores supported the use of Chinese wording of ‘only a little’ (range of median: 12.5–17), ‘moderate’ (range of median: 50–53), and ‘severe’ (range of median: 82.5–90) as the descriptors for the intermediate functional levels of the five EQ-5D dimensions and the label wording of ‘very severe’ (median: 90) to describe the worst level of pain/discomfort and anxiety/depression. CONCLUSIONS: The Chinese version of the EQ-5D-5L comprises descriptors with similar interpretations as those used its English and Spanish counterparts. The response scaling exercise is a useful method for cross-cultural adaptation of health-status instruments.